Associations between force-velocity-power profile in sprinting and ballistic lower limb tests in adolescent elite footballers - Galantine, P.; Bertin, D.; Nicol, C.; Duché, P.; Hays, A. (Sports Biomechanics, 2025)
This study investigated the relationships between performance and force-velocity (F-v) parameters obtained from a ballistic lower limb (BLL) and a 30-m sprint test in 24 adolescent elite footballers (13.2-15.1 years old). In the BLL test, normal ground reaction force and velocity were recorded by two force plates and a linear encoder, respectively, and take-off velocity (vto) at 0% of body mass was considered as performance. In the 30-m sprint test, raw velocity-time data were measured using a radar, and 5, 10 and 30 m sprint times using a timing gate system. Theoretical maximal force (F0), velocity (v0) and power (Pmax) were determined using the Samozino`s method. All sprint times were significantly correlated with vto (p = 0.004 to p < 0.001; -0.57 to -0.72), but no significant correlation was found between the respective F-v parameters ;(p = 0.152 to 0.913). As both tests assess explosive performance, players who can produce a high vto will also perform best in short sprints. However, the F-v discrepancies highlight the complementarity of these tests: the BLL test minimises the coordination and technical influences that can affect sprint performance in adolescents.